A multi-centre prospective evaluation of the Check-Direct ESBL Screen for BD MAX as a rapid molecular screening method for extended-spectrum beta-lactamase-producing Enterobacteriaceae rectal carriage. Issue 3 (November 2017) - Engel, T.; Slotboom, B.J.; van Maarseveen, N.; van Zwet, A.A.; Nabuurs-Franssen, M.H.; Hagen, F.
Summary: Objective: A multiplex extended-spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-E) quantitative polymerase chain reaction (qPCR), performed directly on rectal swabs, was compared with a culture-based protocol to study the discrepancies between the two methods, and identify existing challenges to apply this assay in routine clinical practice. The secondary objective was to assess the performance of the qPCR. Materials and methods: In two Dutch teaching hospitals, 573 rectal swabs were collected prospectively. Culture with additional testing with the Check-MDR CT103XL (Check-Points) was compared with the Check-Direct ESBL Screen for BD MAX (Check-Points), which detects the presence of the ESBL gene families CTX-M1, CTX-M2, CTX-M9 and SHV2/5-ESBL. The culture-based protocol (with Brilliance agar) was considered as the gold standard to assess the performance of the qPCR. Results: Of the 573 rectal swabs, 74 (12.9%) were culture-positive. Eighty-four (14.7%) were qPCR-positive. There were eight culture-positive/qPCR-negative discrepancies and 18 culture-negative/qPCR-positive discrepancies. Sensitivity and specificity of qPCR vs culture were 87.7% [95% confidence interval (CI) 79.7–95.7] and 96.3% (95% CI 94.6–98.0), respectively. Conclusion: The Check-Direct ESBL Screen for the BD MAX is an easy-to-perform, quick molecular diagnostic test with the potential to significantly speed up screening for rectal ESBL-E carriage. Discrepancies were observed between the culture-based protocol and the qPCR in 4.5% of tested samples. Existing challenges for implementing qPCR are its limited sensitivity, the need for thorough knowledge of the local ESBL-E genes, and interpretation of culture-negative but qPCR-positive samples. It is believed that the limited sensitivity of qPCR could be optimized by including bla TEM as a molecular target, and improving the limit of detection.